Avascular necrosis associated with fracture of the femoral neck after hip resurfacing: histological assessment of femoral bone from retrieval specimens. - Steffen, RT; Athanasou, N; Gill, H; Murray, D (2010)
The cause of fracture of the femoral neck after hip resurfacing is poorly understood. In order to evaluate the role of avascular necrosis we compared 19 femoral heads retrieved at revision for fracture of the femoral neck and 13 retrieved for other reasons. We developed a new technique of assessing avascular necrosis in the femoral head by determining the percentage of empty osteocyte lacunae present. Femoral heads retrieved as controls at total hip replacement for osteoarthritis and avascular necrosis had 9% (sd 4; n = 13) and 85% (sd 5; n = 10, p < 0.001) empty lacunae, respectively. In the fracture group the percentage of empty lacunae was 71% (sd 22); in the other group it was 21% (sd 13). The differences between the groups were highly significant (p < 0.001). We conclude that fracture after resurfacing of the hip is associated with a significantly greater percentage of empty osteocyte lacunae within the trabecular bone. This indicates established avascular necrosis and suggests that damage to the blood supply at the time of surgery is a potent risk factor for fracture of the femoral neck after hip resurfacing.